Evidence of a low-carbon tourism paradigm?. Issue 6 (3rd June 2017) - Becken, Susanne
ABSTRACT: The global tourism industry has benefited from exceptional growth; however, a number of challenges have the potential to seriously undermine the industry's future aspirations. This research uses social representation theory to understand how the social group of tourism experts makes sense of the phenomena of "tourism growth", "low-carbon tourism", "peak oil" and "risks for tourism", and whether representations are indicative of different underlying paradigms. A total of 101 experts from various tourism professions and key demographics were interviewed using the free associations method. The findings reveal distinct representations of the four phenomena, but also significant linkages between them, in particular in relation to the global economy, transportation, energy supply and sustainability. Further, whilst experts appear grounded in the Dominant Social Paradigm of consumerism and neoliberal capitalism, there is evidence of alternative views that question some of the fundamental assumptions of the growth paradigm. In particular, when asked about low-carbon tourism and peak oil, experts advanced associations that indicated an Alternative Paradigm. A broader paradigm shift originating from within tourism, however, alone is unlikely.